Pesticides and the immune system : the public health risks - Repetto, Robert (World Resources Institute New YorkUS, 1996)
Addresses a potentially serious risk to public health, the risk that many pesticides affect the human immune system in ways that suppress normal immune responses to invading viruses, bacteria, parasites and tumors.